PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KERJASAMA TIM PADA ANGGOTA SEKOLAH SEPAK BOLA (SSB) TUNAS BANGSA - Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at Soccer School (SSB) Tunas Bangsa Tarai Bangun Village Tambang Subdistrict Kampar Regency located at Jl. Like Karya Perum Griya Tarai Asri Blok A4. The purpose of this research is to know the effect of training and motivation to team work partially and simultaneously on the member of School of Football (SSB) Tunas Bangsa and to know which variable is the most significant influence to team cooperation in School of Football (SSB) Tunas Bangsa. The study population was 17 members of Sekolah Tunak Bangsa Football School (SSB) with census model. The research variables used are training and motivation as independent variable and teamwork as dependent variable. Methods of data analysis using multiple linear regression analysis assisted by SPSS 20 for windows. The results of this study concluded that the training and motivation partially and simultaneously have a significant influence on teamwork at Soccer School (SSB) Tunas Bangsa. Where the most dominant factor influencing teamwork is the training factor. The research that has been conducted in accordance with the regression test (t test) and (f test) shows the independent variables studied is the team cooperation, training and motivation variables have a significant influence on the dependent variable team cooperation